2021
DOI: 10.5195/ijms.2021.1040
|View full text |Cite
|
Sign up to set email alerts
|

Pocket-sized Ultrasound versus Cardiac Auscultation in Diagnosing Cardiac Valve Pathologies: A Prospective Cohort Study

Abstract: Background: Pocket-sized ultrasound devices are used to perform focused ultrasound studies (POCUS). We compared valve malfunction diagnosis rate by cardiac auscultation to POCUS (insonation), both conducted by medical students. Methods: A prospective cohort study was conducted among patients with and without clinically relevant valve dysfunction. Recruitment to the study group was based on the presence of at least one valve pathology of at least moderate severity identified on recent echocardiography stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One pilot study conducted in 2021 used a prospective cohort of three, fourth-year medical students to test their ability to diagnose severe valvular dysfunction using POCUS and auscultation. Their training part of a one-week cardiology clerkship and consisted of 12 hours of handheld ultrasound operation completed in two-hour increments over the course of one month [ 16 ]. These sessions included anatomy lectures, bedside-guided lessons, and review of cases.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One pilot study conducted in 2021 used a prospective cohort of three, fourth-year medical students to test their ability to diagnose severe valvular dysfunction using POCUS and auscultation. Their training part of a one-week cardiology clerkship and consisted of 12 hours of handheld ultrasound operation completed in two-hour increments over the course of one month [ 16 ]. These sessions included anatomy lectures, bedside-guided lessons, and review of cases.…”
Section: Reviewmentioning
confidence: 99%
“…The authors concluded that in the three students tested, POCUS was significantly better for diagnosing a combination of valvular malfunctions in the same patient when compared to auscultation. These conclusions were based on diagnostic sensitivity and specificity, calculated via SPSS version 18 software [ 16 ]. Although the small sample size in this study poses a significant limitation, these preliminary results warrant further studies that expand on these conclusions.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown that POCUS is superior to conventional auscultation for diagnosing valvular heart disease, even when performed by non-cardiologists. Examination with POCUS has been shown to improve the diagnostic accuracy of valvular heart disease by 50% to 80% in as little as 15 minutes after the start of the physical examination, even in final-year medical students increasing their percentage of valvular heart disease detection [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…For cardiac applications, POCUS devices have been used to evaluate aortic stenosis with anticipation of expanded utility to assess stenosis of other cardiac valves [66]. Direct training using a POCUS device allowed for increased diagnostic accuracy from younger medical students in comparison to traditional cardiac auscultation [67]. Additional case studies have also demonstrated the utility of POCUS devices not only for the cardiac system but also in the vasculature, whether it be for peripheral artery disease or aneurysms [68,69].…”
Section: Clinical Applications Of Pocus In Lrsmentioning
confidence: 99%